Model Pengambilan Keputusan Pemilihan Rumah KPR dengan Metode Analytical Hierarchy Process (AHP) - Danu, Muhammad; Patradhiani, Rurry; Putri, Anindita Rahmalia; Histiarini, Aprisa Rian (Metode : Jurnal Teknik Industri, 2025)
The growing demand for housing in Palembang has encouraged people to purchase homes through the Mortgage Ownership Program (Kredit Pemilikan Rumah/KPR). The complexity of the purchasing decision arises from the many factors that must be considered, such as building type and quality, location, price, and environmental conditions. This study aims to identify the main criteria in selecting KPR housing in Palembang and to determine the priority of each criterion. The method employed is the Analytical Hierarchy Process (AHP), with a case study conducted at PT. Rama Trimitra Development Group. Research data were collected through questionnaires distributed to expert respondents consisting of developers, architects, and banking representatives. The results show that the environmental criterion is the top priority with an average weight of 0.2962, followed by location, price, and building type and quality, which ranked the lowest. These findings are expected to assist prospective homeowners in making better purchasing decisions and to serve as a reference for developers in designing KPR housing products that align with consumer expectations.